GAMBARAN STRES AKADEMIK SAAT PEMBELAJARAN JARAK JAUH (PJJ) PADA SISWA DI SMK NEGERI 1 GODEAN TAHUN PELAJARAN 2020/2021 - Tati Indriani (Ristekdik : Jurnal Bimbingan dan Konseling, 2021)
Academic stress is one of the problems experienced by students due to academic pressure to get a score that is in accordance with the Minimum Completeness Standard (SKM), coupled with current conditions that make students have to do distance learning. This study aims to determine the level of academic stress of students at SMK Negeri 1 Godean. This research uses descriptive quantitative method. The population of this research is all students of SMK Negeri 1 Godean. The random sampling technique was used in this research, so that the sample size was 352 students. The results showed that the academic stress of students of SMK Negeri 1 Godean was more in the high category as many as 182 students or 51.7%. Based on the four aspects of academic stress, there are psychological, physiological, and cognitive aspects that show high categories, while behavior aspects are in the low category.